Program Bincang Santai dalam Transportasi Publik - Salman Al Hafizh; Zulfe briges (UNISBA Press, 2023)
Abstract. Today Indonesia has a very rapid development of the transportation system, one of the actors behind the development of the transportation system is PT. Indonesian Railways (PT KAI or KAI). The large number of PT KAI's consumers in Indonesia have narrowed down to consumers who like and have an interest in trains, they are usually called railfans. To strengthen the lines of communication between railfans and PT KAI, PT KAI's public relations team organizes a routine activity program with railfans, namely